Quality- and profit-oriented scheduling of flexible resource-constrained projects - Carolin Kellenbrink; Stefan Helber (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2014)
We study the problem of determining both the structure and the schedule of projects subject to capacity constraints. We assume that those projects are flexible in the sense that the activities to be implemented are not entirely known in advance. In such a setting, decisions must be made with respect to the implementation of the optional activities. Such decisions affect the duration, cost, quality and eventual revenue of the project. Examples of this type of problem can often be found when complex capital goods such as aircraft engines are overhauled, when buildings are renovated to meet higher environmental and efficiency standards, or in productdevelopment processes. We describe the problem, develop a mixed-integer optimisation model, explain specific features of a genetic algorithm to solve the problem and report the results of a numerical study.
Keywords: 330; quality; project scheduling; genetic algorithm; RCPSP; flexible projects